Rapid Identification of the Chemical Components of Ilex rotunda Thunb Using UPLC-Q-TOF-MS/MS - Xinxin Chen; Junmao Li; Renyikun Yuan; Youqiong Zhuo; Yangling Chen; Chenwei Zhang; Ming Chen; Hong-Wei Gao; Zhenjie Liu; Yulin Feng; Zheng-Tao Wang; Shilin Yang (Journal of Chemistry)
Ilicis Rotundae Cortex (IRC) consists of the bark of Ilex rotunda Thunb, and its chemical constituents mainly include flavonoid glycosides, phenols, and triterpenoid saponins. In this study, a preliminary analysis was performed to identify and obtain the chemical components from IRC to better control the quality of the medicinal materials and provide a chemical basis for the study of the efficacy of the active components. Simple and efficient sample pretreatment and ultrasonic-assisted extraction methods were used to analyze the mass spectrum fragments and fracture modes in the anion mode by UPLC-Q-TOF-MS/MS. Using a two-step strategy, the neutral loss, diagnostic ions, and characteristic fragments were studied to screen diverse skeletons and substitutions, and the possible compounds were identified by comparison with databases. The representative compounds were compared with the standard, and the mass spectrogram was found to match perfectly. Thus, our findings reveal that this method is feasible and reliable and can be used to analyze the chemical components of IRC. We identified 105 compounds, including 22 triterpenoid saponins, 15 chlorogenic acids, 33 phenylpropanoids and phenylpropanosides, 3 iridoids, 1 flavonoid, 10 lignans, 12 glycosides, and 9 other compounds. This method lays the foundation for further elucidating the pharmacodynamics of IRC and provides a practical method for the identification of IRC.